Governing By Data: A Critical Analysis of Big Data’s Role in Urban Public Policy and Social Stratification in Southeast Asian Megacities - Luca Santi; Martina Rossi; Giuseppe Lazzari (Yayasan Adra Karima Hubbi, 2025)
Background. The rapid expansion of big data infrastructures in Southeast Asian megacities has reshaped the formulation and implementation of urban public policy, raising concerns about algorithmic governance and emerging forms of social stratification. Urban administrations increasingly rely on predictive analytics, biometric systems, and real-time surveillance tools to guide decision-making, yet the socio-political implications of these technologies remain insufficiently understood. Purpose. This study aims to critically examine how big data systems influence policy priorities, resource allocation, and the lived experiences of marginalized urban communities. Method. . A qualitative research design was employed, combining policy document analysis, expert interviews, and digital ethnography across three major Southeast Asian cities. Results. The findings reveal that big data governance enhances administrative efficiency but simultaneously reinforces structural inequalities through opaque categorization practices, risk scoring models, and selective visibility regimes. These mechanisms privilege affluent districts while amplifying precarity in low-income urban populations. Conclusion. The study concludes that big data functions as both a technocratic tool and a political instrument, producing uneven urban outcomes shaped by existing socio-economic hierarchies. The results underscore the need for transparent data governance frameworks and equity-oriented urban policy reforms.